Characterization of Enhancing MS Lesions by Dynamic Texture Parameter Analysis of Dynamic Susceptibility Perfusion Imaging. (13th January 2016) - Verma, Rajeev K.; Slotboom, Johannes; Locher, Cäcilia; Heldner, Mirjam R.; Weisstanner, Christian; Abela, Eugenio; Kellner-Weldon, Frauke; Zbinden, Martin; Kamm, Christian P.; Wiest, Roland
Abstract : Purpose . The purpose of this study was to investigate statistical differences with MR perfusion imaging features that reflect the dynamics of Gadolinium-uptake in MS lesions using dynamic texture parameter analysis (DTPA). Methods . We investigated 51 MS lesions (25 enhancing, 26 nonenhancing lesions) of 12 patients. Enhancing lesions (n = 25 ) were prestratified into enhancing lesions with increased permeability (EL+; n = 11 ) and enhancing lesions with subtle permeability (EL−; n = 14 ). Histogram-based feature maps were computed from the raw DSC-image time series and the corresponding texture parameters were analyzed during the inflow, outflow, and reperfusion time intervals. Results . Significant differences (p < 0.05 ) were found between EL+ and EL− and between EL+ and nonenhancing inactive lesions (NEL). Main effects between EL+ versus EL− and EL+ versus NEL were observed during reperfusion (mainly in mean and standard deviation (SD): EL+ versus EL− and EL+ versus NEL), while EL− and NEL differed only in their SD during outflow. Conclusion . DTPA allows grading enhancing MS lesions according to their perfusion characteristics. Texture parameters of EL− were similar to NEL, while EL+ differed significantly from EL− and NEL. Dynamic texture analysis may thus be further investigated as noninvasive endogenous marker of lesion formation and restoration.